Some indirect testimonies about Plato’s personal character and their connection with passages of the written dialogues - Spinassi, Miguel Ángel (Revista Archai, 2018)
This article aims to contribute to the image of the historical Plato. For this purpose, I have selected from the indirect tradition favorable to Plato nine testimonies, which shed some light on his personal character. I believe that this favorable tradition would represent more faithfully the philosopher of Athens than the hostile one. That is why I have tried to draw attention in the second part of the article on the possible connection between those indirect testimonies and some passages from the written dialogues. In fact, Plato’s benevolence and good disposition towards other people would correspond to those attitudes that are required from the interlocutor as preconditions for dialectic conversation. I suggest, finally, that both the personality of Plato and his work would be in harmony and that a key aspect of this harmony is represented by the positive and favorable predisposition towards others.